Online discussion forums for rural teacher professional development - Ikhsanudin Ikhsanudin (Journal on English as a Foreign Language, 2021)
Rural teachers often have difficulties to participate conventionally in professional development programs in towns. This article explains the possibility and challenge of developing an online e-learning program and forum to support rural English teacher capacity building. The research was conducted through a qualitative survey in four districts in two of fourteen counties in Kalimantan Barat province, Indonesia. The data were collected through interview and observation and were analyzed using a three-level classification system that consisted of unidimensional description, multidimensional description, and explanation. The research found that the government regulations, the transportation infrastructure, the internet connection, and the teacher readiness could support the online discussion forum. The possible design to support the forum was an asynchronous discussion forum in social media groups. The challenge was finding motivated and committed teachers to initiate and lead the forums. Based on the discussion and conclusion, the research recommends that external experts mentor the leaders in the first year. When the leaders are ready to manage the groups, the mentor can motivate the leaders to manage the groups autonomously and may collaborate with the external experts to conduct some relevant professional development programs.